Health Literacy and Adherence to Therapy in Type 2 Diabetes: A Cross-Sectional Study in Portugal - Simone Rodrigues; Ana Isabel Patrício; Cátia Cristina; Flávia Fernandes; Gisela Marcelino Santos; Inês Antunes; Inês Pintalhão; Marília Ribeiro; Rita Lopes; Silvana Moreira; Sofia A. Oliveira; Susana Pereira Costa; et al. (SLACK Incorporated, 2024)
Background Therapy adherence is a key factor in the control of type 2 diabetes mellitus (T2DM). Optimal self-care requires skills in health literacy (HL). Objective This study aims to analyze the relationship between HL and adherence to therapy and to understand the possible influence of other sociodemographic and disease variables. Methods A multicenter, cross-sectional study was conducted in Portuguese in 13 different primary health care units in both rural and urban environments. A sociodemographic questionnaire and two validated instruments, "Medical Term Recognition Test" and "Summary of Diabetes Self-Care Activities," were applied. The last value of hemoglobin A1c (HbA1c) and the number of chronic medications were collected from clinical records. Descriptive statistics and bivariate correlations were performed as well as multivariable linear regression to assess the association between HL and adherence to therapy. Key Results Participants (n = 354) were on average age 63.67 ± 10.39 years, 57.1% male and 42.9% female, 68.4% with inadequate HL and an average HbA1c of 7 ± 1.18%. Better HL was correlated with higher adherence to the total of self-care activities, nonpharmacological therapy, and foot care. In multivariable linear regression analyses, better HL (β = 0.176, p = .003), less than minimum wage (β = −0.197, p = .001) and insulin therapy (β = 0.272, p = .001) were independently associated with increased adherence to overall self-care activities. Conclusion In a representative sample of people with T2DM in Portugal, HL was a key factor for greater adherence to demanding self-care activities. [HLRP: Health Literacy Research and Practice. 2024;8(4):e194-e203.]